Layered Lanthanide Sulfophosphonates and Their Proton Conduction Properties in Membrane Electrode Assemblies - Bazaga-García, Montse; Salcedo, Inés R.; Pérez-Colodrero, Rosario Mercedes; Xanthopoulos, Konstantinos; Villemin, Didier; Stock, Norbert; López-González, Mar; Del Río, Carmen; Ramírez-Losilla, Enrique; Cabeza-Díaz, Aurelio; Demadis, Konstantinos D.; Olivera-Pastor, Pascual (ACS publications, 2019)
Metal phosphonates containing acidic groups exhibit a wide range of proton conduction properties, which may enhance the performance of membrane electrode assemblies (MEAs). In this work, focus is placed on proton conduction properties of coordination polymers derived from the combination of lanthanide ions with a phosphonate derivative of taurine (2-[bis(phosphonomethyl)amino]-ethanesulfonic acid, H5SP). High-throughput hydrothermal screening (140 °C) was used to reach optimal synthesis conditions and access pure crystalline phases. Seven compounds with the composition Ln[H(O3PCH2)2−NH−(CH2)2−SO3]·2H2O were isolated and characterized, which crystallize in two different structures, monoclinic m-LaH2SP and orthorhombic o-LnH2SP (Ln = Pr, Nd, Sm, Eu, Gd, and Tb), with unit cell volumes of ∼1200 and ∼2500 Å3, respectively. Their crystal structures, solved ab initio from X-ray powder diffraction data, correspond to different layered frameworks depending on the Ln3+ cation size. In the orthorhombic series, o-LnH2SP, the sulfonate group is noncoordinated and points toward the interlayer space, while for m-LaH2SP, both phosphonate and sulfonate groups coordinate to the Ln3+ centers. As a consequence, different H-bonding networks and proton transfer pathways are generated. Proton conductivity measurements have been carried out between 25 and 80 °C at 70−95% relative humidity. The Sm3+ derivative exhibits a conductivity of ∼1 × 10−3 S·cm−1 and activation energy characteristic of a Grotthuss-type mechanism for proton transfer. Preliminary MEA assays indicate that these layered lanthanide sulfophosphonates assist in maintaining the proton conductivity of Nafion membranes at least up to 90 °C and perform satisfactorily in single proton-exchange membrane fuel cells.
Keywords: Pilas de combustible; Baterías de estado sólido; Conductividad eléctrica; Catalizadores; Flúor - Compuestos; Nafion membranes; proton conductivity; Sulfophosphonates; Proton-conductivity; High-throughput; Membrane electrode assemblies